Naming of Islands and Mountains in the Sangihe Talaud Islands Region: A Toponymy Study - Pareda, Herol H; Panambunan, Emelia J.C (Journal Corner of Education, Linguistics, and Literature, 2025)
This research focused on the toponymy study, etymology, endonym and exonym which are related to the names of island and mountain in Sangihe Talaud archipelagos. This research is descriptive research. The data were collected from library research and field research in Sangihe island. The result of this research would be described as follow: the toponymy etymology study derived from folklore, legend, and history. Sangihe island has endonym such as sangihe and tampungan lawo. Besides, Sangihe island has variative exonym such as zanger,sanger, sangir, sanguin, sangil, and sangi. Talaud island has endonym such as talroda,and taloda and the exonym of this island such as paradise, talaud and porodisa. Siau island has endonym such as siawu, and karangetang and the exonym of Siau island is sio,siau siouw, siauw, chiaoa, shao, and siaw. Tagulandang island has endonym such as mandolrokang and tagulrandang and the exonym of this island is mandolokang, tagulandang, pagincar and pancare. Biaro island has endonym such as biaro and kolro-kolro and the exonym of this is Biaro and kolo-kolo. Furthermore, the researcher found that Awu mount has endonym such awu, manakanusa and aditinggi. Karangetang mount has endonym such as karangetang, simeno-meno makiseba and aditinggi and its exonym is yohanes tamanggaholo and api Siau. Whereas Tamata Mount only has one endonym its called tamata and has one exonym such as Yohana mount. Ruang mount has endonym such ruang and aditinggi, and its exonym is duang.